Workspace Analysis of a 7R Manipulator with Link Offset - Wang Yongjie; Fu Tie; Liu Yujia; Zhu Zhaohui (Jixie chuandong)
Aiming at a 7R manipulator with link offset at the shoulder,the forward position solution model is established by suing D- H method and the model is solved. Based on this,the workspace is studied and analyzed with Monte- Carlo method and the robotic workspace is drawn in Matlab software,meanwhile,the result is validated with geometric method. The result shows that Monte- Carlo method in solving the workspace of manipulator has its effectiveness and effectiveness,and it provides the reference for similar multi- joint manipulator.